Calidad bacteriológica de carne cruda fresca de Arapaima gigas “paiche” comercializada en el mercado belén y modelo. Iquitos, Perú - Acho Shapiama, Juan Miguel (2024)
This study was carried out from October 10, 2022 to March 3, 2023, with the purpose of evaluating the bacteriological quality of fresh raw meat of Arapaima gigas "paiche" marketed in the Belén and Modelo market Iquitos-Peru. 40 samples were randomly selected, equivalent to 400g, the following methods were used, standard plate count calculation for mesophilic aerobic bacteria, in addition the bacteriological indicators were; Determination of Escherichia coli presumptive and confirmatory phase, isolation of coagulase-positive Staphylococcus aureus, and finally the method was detection of Salmonella sp. The presence of mesophilic aerobic bacteria concentrated in the stalls of the Modelo market, higher than 21 x 106 CFU/g, and in the Belén market it was 20 x 105 CFU/g. Escherichia coli was present in 10 samples from the Modelo market, equivalent to 41.7%, and 14 samples in the Belén market, with a value of 58.3%. Likewise, Staphylococcus aureus had the highest positivity rate in the Modelo market, with 19 positive samples, equivalent to 73.1% of the samples. However, Salmonella sp was more present in the Belén market, with 15 positive samples, with a value of 44.4%. It was concluded that the samples of fresh raw meat of Arapaima gigas paiche in both markets had inadequate bacteriological quality, since there was a quantity of bacteria that exceeded the permitted limits, unfit for human consumption. This indicates that the product was kept in inadequate handling and/or storage conditions.